2021
DOI: 10.3390/min11040432
|View full text |Cite
|
Sign up to set email alerts
|

Carbon-Assisted Bioleaching of Chalcopyrite and Three Chalcopyrite/Enargite-Bearing Complex Concentrates

Abstract: Overcoming the slow-leaching kinetics of refractory primary copper sulfides is crucial to secure future copper sources. Here, the effect of carbon was investigated as a catalyst for a bioleaching reaction. First, the mechanism of carbon-assisted bioleaching was elucidated using the model chalcopyrite mineral, under specified low-redox potentials, by considering the concept of Enormal. The carbon catalyst effectively controlled the Eh level in bioleaching liquors, which would otherwise exceed its optimal range … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Where Eh naturally increases in the system due to the presence of “strong” Fe-oxidisers, the carbon catalyst can effectively suppress and control the Eh level in the bioleach liquors because the carbon catalyst surface acts as an electron mediator to couple the reduction of Fe 3+ ( Uchida et al, 2000 ) and the oxidation of reduced inorganic sulfur compounds (RISCs). The Eh level was thus controlled by counterbalancing microbial Fe 2+ oxidation ( Oyama et al, 2020 , 2021 ;). The effect of activated carbon has also been reported in the bioleaching of low-grade primary Cu sulfide ores ( Zhang and Gu, 2007 ).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Where Eh naturally increases in the system due to the presence of “strong” Fe-oxidisers, the carbon catalyst can effectively suppress and control the Eh level in the bioleach liquors because the carbon catalyst surface acts as an electron mediator to couple the reduction of Fe 3+ ( Uchida et al, 2000 ) and the oxidation of reduced inorganic sulfur compounds (RISCs). The Eh level was thus controlled by counterbalancing microbial Fe 2+ oxidation ( Oyama et al, 2020 , 2021 ;). The effect of activated carbon has also been reported in the bioleaching of low-grade primary Cu sulfide ores ( Zhang and Gu, 2007 ).…”
Section: Introductionmentioning
confidence: 99%
“…This is due to the passivation of the enargite surface by Fe(III)-bearing minerals formed during the dissolution of pyrite. Our previous studies have shown that as a compromise to mitigate this competition effect, suppressing the Eh value to around <700 mV is preferable to maintain a more stable and prolonged Cu dissolution from enargite while minimising the passivation effect of Fe(III)-bearing minerals, allowing better control of the leaching process and Cu recovery ( Oyama et al, 2018 , 2020 , 2021 ; Okibe et al, 2022 ). Accordingly, the need for Eh control is different for chalcopyrite and enargite.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations